Development of Learning Media Using Cartoon Picture Media in Improving Students’ Interest in Learning and Pouring Out Ideas Class XII State Vocational School 1 Lolofitu MOI - Waruwu, Derman Jaya; Kartolo, Rahmat (PT Inovasi Pratama Internasional, 2025)
This study aims to examine the application of caricature drawing media in learning for Class XII students at SMK Negeri 1 Lolofitu Moi during the 2024–2025 academic year. The research focuses on (1) the feasibility of using caricature drawing media, (2) how to effectively implement it, and (3) whether it enables students to express their ideas more effectively. The study employs Classroom Action Research (PTK) conducted in cycles, including planning, implementation, observation, and reflection. Data collection was carried out using essay tests, and both qualitative and quantitative analysis techniques were applied. The results indicate an increase in student engagement in learning. In cycle I, 20.00% of students actively participated, which rose to 60.00% in cycle III. Furthermore, the students' ability to use caricature drawing media improved significantly. The average learning outcomes increased from 46.29 in cycle I to 75.43 in cycle II, a gain of 29.14 points, and further increased to 82.57 in cycle III, marking a total improvement of 36.29 points. These findings suggest that caricature drawing media is effective in enhancing student engagement and learning outcomes, making it a viable tool for creative and interactive learning.